2015
DOI: 10.1098/rsif.2015.0254
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the chemical and biological functionalization of scaffolds for cardiac tissue engineering: a review

Abstract: The development of biomaterials for cardiac tissue engineering (CTE) is challenging, primarily owing to the requirement of achieving a surface with favourable characteristics that enhances cell attachment and maturation. The biomaterial surface plays a crucial role as it forms the interface between the scaffold (or cardiac patch) and the cells. In the field of CTE, synthetic polymers ( polyglycerol sebacate, polyethylene glycol, polyglycolic acid, poly-L-lactide, polyvinyl alcohol, polycaprolactone, polyuretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
233
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(242 citation statements)
references
References 284 publications
(371 reference statements)
0
233
0
9
Order By: Relevance
“…The synchronic effect of electrospinning and plasma grafting was recently associated with several advances in the TE field. This was illustrated by the significant enhancement of several cellular activities when plasma grafts biomolecules such as ECM components and growth factors on nanofibers [13,71]. Both plasma grafting and plasma polymerization techniques are considered superior to the plasma activation in terms of ageing effect.…”
Section: Plasma Polymerization and Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…The synchronic effect of electrospinning and plasma grafting was recently associated with several advances in the TE field. This was illustrated by the significant enhancement of several cellular activities when plasma grafts biomolecules such as ECM components and growth factors on nanofibers [13,71]. Both plasma grafting and plasma polymerization techniques are considered superior to the plasma activation in terms of ageing effect.…”
Section: Plasma Polymerization and Graftingmentioning
confidence: 99%
“…To this end, different surface modification techniques have been performed such as ion-beam, X-ray, gamma radiation, wet chemical treatment and plasma-based techniques [12]. Specific bioactive molecules can be grafted onto the surface after modifying its chemistry or can be blended with the polymer solution prior to the electrospinning [13]. Plasma surface engineering of electrospun materials has known an abrupt rise during the past decade due to its potential to selectively modify the surface chemistry with a precise control of all the process parameters to avoid the damage of the delicate nanofibrous structure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The process of functional tissue reconstruction, however, may be distinct and not recapitulate the original developmental progression, as in the case of direct versus endochondral ossification. These tissue replacement processes may utilize classic tissue engineering approaches, using biodegradable polymers 126 or hydrogels, 127 to provide a scaffold for cell ingrowth. These biomaterials may not only help promote cell differentiation and matrix synthesis, but may facilitate spatial patterning of tissues.…”
Section: Translating Epimorphic Regenerationmentioning
confidence: 99%
“…The results showed that adult rabbit cardiomyocytes atached to the scafold exhibited growth and cell organization comparable to that found in native myocardium [5]. The main beneits of synthetic materials are their strength and durability, although their biocompatibility tissues and surface properties, which are generally poor to achieve a favourable environment for cell atachment [58]. Toxicity is the outmost concern with synthetic materials, especially in the case of biodegradable materials, which can release potentially harmful by-products of degradation into the body.…”
Section: Tissue Regeneration: a Biomimetic Designmentioning
confidence: 62%
“…Nonetheless, the major drawback with this method remains the inability to generate patches with sizable thickness due to difusion limitations. The biomaterial surface plays a crucial role as it forms the interface between the scafold (or cardiac patch) and the cells [58]. The cells once implanted inside the scafold will help the body heal itself [28,116].…”
Section: Cardiac Patches: In Situ Tissue Regenerationmentioning
confidence: 99%